Purchasing Decision Delivery Service KURIRMU in Surabaya - Moh Husnan; Ani Wulandari; Arasy Alimudin (NAROTAMA UNIVERSITY, Indonesia, 2021)
This study aims to determine the effect of the independent variables Electronic Word of Mouth, Price and Service Quality on the dependent variable of the decision to use KURIRMU delivery services in Surabaya. The research approach used is non-probability sampling with purposive sampling method. The population in this study were KURIRMU service users for the last six months and the respondents in this study were over 17 years old and the sample used was 96 respondents. The data of this research is quantitative by collecting data with a questionnaire. The data analysis technique used is multiple linear regression. The results of this study indicate that Electronic Word of Mouth, price partially has a positive and significant effect on purchasing decisions. However, the service quality variable partially has no significant effect on purchasing decisions. Electronic Word of Mouth, Price and Service Quality simultaneously have a positive and significant effect on purchasing decisions.